Errorless Learning and Spaced Retrieval Training for Clients with Alzheimer's Dementia. (1st September 2013) - Crowe, Jessica; Gabriel, Linda
ABSTRACT Clients with Alzheimer's dementia (AD) may experience limitations in completing activities of daily living (ADL) due to impairments in cognition, memory, and problem-solving. These clients are often referred to occupational therapy (OT) services in order to maximize independence in ADL and decrease caregiver burden. Occupational therapists may be challenged when developing treatment interventions for clients with AD due to client deficits in memory and learning. This article explores evidence-based learning strategies—errorless learning (EL) and spaced retrieval (SR)—to improve learning and memory and OT outcomes for clients with AD. The roles of memory and learning are discussed, and EL and SR strategies are explored for clients with AD. OT intervention ideas are identified, and strategies for integrating EL and SR techniques into the OT plan of care (POC) are also discussed. Future research implications are explored for expanding evidence for EL and SR as part of the OT POC.